DPP4, the Middle East Respiratory Syndrome Coronavirus Receptor, is Upregulated in Lungs of Smokers and Chronic Obstructive Pulmonary Disease Patients. (17th August 2017) - Seys, Leen J M; Widagdo, W; Verhamme, Fien M; Kleinjan, Alex; Janssens, Wim; Joos, Guy F; Bracke, Ken R; Haagmans, Bart L; Brusselle, Guy G
Abstract : The MERS coronavirus receptor, dipeptidyl peptidase 4 is upregulated in the lungs of smokers and chronic obstructive pulmonary disease (COPD) patients. This offers a potential mechanism for the increased susceptibility of smokers and COPD patients for MERS-CoV infection. Abstract: Background: Middle East respiratory syndrome coronavirus (MERS-CoV) causes pneumonia with a relatively high case fatality rate in humans. Smokers and chronic obstructive pulmonary disease (COPD) patients have been reported to be more susceptible to MERS-CoV infection. Here, we determined the expression of MERS-CoV receptor, dipeptidyl peptidase IV (DPP4), in lung tissues of smokers without airflow limitation and COPD patients in comparison to nonsmoking individuals (never-smokers). Methods: DPP4 expression was measured in lung tissue of lung resection specimens of never-smokers, smokers without airflow limitation, COPD GOLD stage II patients and in lung explants of end-stage COPD patients. Both control subjects and COPD patients were well phenotyped and age-matched. The mRNA expression was determined using qRT-PCR and protein expression was quantified using immunohistochemistry. Results: In smokers and subjects with COPD, both DPP4 mRNA and protein expression were significantly higher compared to never-smokers. Additionally, we found that both DPP4 mRNA and protein expression were inversely correlated with lung function and diffusing capacity parameters. Conclusions: We provide evidence that DPP4 is upregulated in the lungs of smokers and COPD patients, which could partially explain why these individuals are more susceptible to MERS-CoV infection. These data also highlight a possible role of DPP4 in COPD pathogenesis.